2011
DOI: 10.1177/1534735411403306
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides Suppress Growth of Human Oral Cancer SAS Cells In Vitro and in a Murine Xenograft Model

Abstract: Purpose. Gypenosides (Gyp) are the major components of Gynostemma pentaphyllum Makino. The authors investigated the effects of Gyp on cell morphology, viability, cell cycle distribution, and induction of apoptosis in human oral cancer SAS cells and the determination of murine SAS xenograft model in vivo. Experimental design. Flow cytometry was used to quantify the percentage of viable cells; cell cycle distribution; sub-G1 phase (apoptosis); caspase-3, -8, and -9 activity; reactive oxygen species (ROS) product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…seeds showed anti-tumor activities under in-vivo conditions (Atashrazm et al, 2016; Liu G. et al, 2016; Zheng et al, 2016; Wang et al, 2017). One latest review updated the anti-cancerous potential of gynostemma polysaccharide in different normal and transgenic cancer mice models (Hsu et al, 2011; Lu et al, 2012; Liu et al, 2014; Tai et al, 2016). Thus, in-vivo studies using tested polysaccharide fractions at the next level would generate their comprehensive efficacy report for better prediction of their anti-cancerous potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…seeds showed anti-tumor activities under in-vivo conditions (Atashrazm et al, 2016; Liu G. et al, 2016; Zheng et al, 2016; Wang et al, 2017). One latest review updated the anti-cancerous potential of gynostemma polysaccharide in different normal and transgenic cancer mice models (Hsu et al, 2011; Lu et al, 2012; Liu et al, 2014; Tai et al, 2016). Thus, in-vivo studies using tested polysaccharide fractions at the next level would generate their comprehensive efficacy report for better prediction of their anti-cancerous potential.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has reported the anti-cancerous mechanism of Gynostemma pentaphyllum (Thunb.) Makino (Jiaogulan) GPM polysaccharides through cell cycle arrest (modulation of several cell cycle regulatory proteins (CDK-2, CDK-4, and CDK-6) (Chen et al, 2009; Cheng et al, 2011), induction of apoptosis (regulation of anti-apoptotic proteins Bcl-2, Bcl-xl and pro-apoptotic proteins Bax, Bad, and Bak (Wang et al, 2002; Hsu et al, 2011; Lin et al, 2011; Lu et al, 2012), glycolysis inhibition and immunomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides (GP) are saponins of Gynostemma pentaphyllum, a traditional Chinese medicinal herb in the treatment of chronic inflammation, hyperlipidemia, and cardiovascular disease. GP has been demonstrated by the modern scientific methods to possess a variety of pharmaceutical properties such as anti-tumor (Lu et al 2012), antihyperlipidemia (Megalli et al 2005), and anti-hepatic fibrosis . GP can also exert cardioprotective effects in rats with induced myocardial infarction by preserving the activity of superoxide dismutase (SOD) and reducing the level of malondialdehyde (MDA) in the myocardium (Xiong et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides (Gyp), the major components extracts from Gynostemma pentaphyllum (Thunb.) Makino, exists mainly as dammarane-type triterpene glycosides ( Fig 1A ) and has been used as a traditional popular folk medicine in Asia for centuries to treat cancer [ 11 13 ], hyperlipoproteinemia [ 14 ], hepatitis [ 15 ], and cardiovascular disease [ 16 ]. Experimental study has reported that Gyp could trigger apoptosis in human colorectal cancer 205 cells through mitochondria-dependent pathway and activation of caspase-3 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%